1995
DOI: 10.1111/j.1365-2133.1995.tb02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of the bullous pemphigoid-180 antigen in normal and neoplastic epithelia

Abstract: BP180 is a 180kDa hemidesmosomal protein recognized by bullous pemphigoid (BP) and pemphigoid gestationis (PG) autoantibodies. Recent cloning and sequence analysis performed by our laboratory have revealed that BP180 is a transmembrane protein with a long extracellular collagen-like region. A rabbit polyclonal antibody has been generated against a recombinant protein, designated GST-N delta 1, containing a segment of the BP180 ectodomain. The resulting antiserum, RN delta 1A, was shown to specifically react wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Nevertheless, in the yeast two-hybrid system, the interactions must occur between discrete individual polypeptides, since the interacting clones in the activation domain were retransformed, and the interactions were confirmed using purified plasmids. Previous studies have clearly demonstrated that BPAG2 is the major component of hemidesmosomes at the dermal-epidermal basement membrane zone, while immunohistochemical analyses have suggested more widespread distribution [Nishizawa et al, 1993;Fairley et al, 1995]. Utilizing multiple-tissue mRNA blots and multi-tissue cDNA panels, we demonstrated that BPAG2 is expressed in a variety of tissues with prominent epithelial component.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, in the yeast two-hybrid system, the interactions must occur between discrete individual polypeptides, since the interacting clones in the activation domain were retransformed, and the interactions were confirmed using purified plasmids. Previous studies have clearly demonstrated that BPAG2 is the major component of hemidesmosomes at the dermal-epidermal basement membrane zone, while immunohistochemical analyses have suggested more widespread distribution [Nishizawa et al, 1993;Fairley et al, 1995]. Utilizing multiple-tissue mRNA blots and multi-tissue cDNA panels, we demonstrated that BPAG2 is expressed in a variety of tissues with prominent epithelial component.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the epithelial basement membranes of cornea [Gordon et al, 1997], ocular conjunctiva, buccal mucosa, upper esophagus, placenta, umbilical cord, and transitional epithelium of the bladder have been shown to express BPAG2, when examined by immunofluorescence staining with antibodies recognizing BPAG2 epitopes [Fairley et al, 1995]. However, the expression of the corresponding gene at the mRNA level has not been examined in detail.…”
mentioning
confidence: 97%
“…Transmembrane collagen XVII, also known as BP180 or BPAG2, is widely expressed in skin (6)(7)(8), cornea (7,9), teeth (10), buccal and esophageal mucous membranes (7), brain (11), placenta, and umbilical cord (7). Among these tissues, collagen XVII plays the most important role in the skin, where it is a component of hemidesmosomes in basal keratinocytes and provides stable adhesion between the epidermis and the dermis.…”
mentioning
confidence: 99%
“…As it was demonstrated that expression of BP180 was decreased or absent in cutaneous neoplasms [184], some authors speculated that some type of carcinomas itself might expose BP180 antigenic epitope, which would normally be hidden, thus inducing the production of autoantibodies that lead to the onset of BP [185]. It was proposed that BP180 neoexpression could be associated with early/malignant transformation of keratinocytes as widely expression of BP180 was demonstrated in SCC in contrast to normal skin, where this protein is restricted to basal keratinocytes [186].…”
Section: Malignancy In Relation Tomentioning
confidence: 98%